Novel platelet-rich plasma/ hyaluronic acid lyophilized formulations for wound healing applications - D’Agostino, Antonella; d’Agostino, Maria; Nardini, Marta; Muraglia, Anita; Di Meo, Celeste; Mastrogiacomo, Maddalena; Schiraldi, Chiara (Frontiers in Bioengineering and Biotechnology, 2025)
Platelet-rich plasma (PRP) is a well-known biological product used in regenerative medicine. One of the limitations of its clinical use is the need for surgeons to obtain ready-to-use preparations. A lyophilized formulation with specific and reproducible levels of growth factors can, therefore, be considered a significant improvement for tissue regeneration. Therefore, it is of great interest to develop a formulation that enables the prolonged release of the growth factors and bioactive components present in PRP while improving the stability of these biomolecules during storage. To this aim, specific preparations obtained by mixing hyaluronic acid (HA) of low–medium molecular weight (56 or 200 kDa) with PRP were lyophilized to achieve an “off-the-shelf” product. These formulations were characterized from both biophysical and biological perspectives. Primary human dermal fibroblast proliferation and time-lapse scratch assays were performed on freshly lyophilized formulations and during storage at different temperatures (4°C and 25°C) to assess their biological activity upon resuspension for up to 6 months. Gene and protein expressions of collagen type 1 and elastin at time zero were evaluated. Platelet-Derived Growth Factor (PDGF)-BB and Vascular Endothelial Growth Factor (VEGF) releases were measured using the ELISA assay. All HA/PRP formulations were able to induce cell proliferation compared to PRP alone. HA/PRP formulations exhibited a superior repair rate compared to PRP in the scratch assay, confirming HA’s ability to improve fibroblast migration. In the presence of HA, 80% of wound closure was achieved within 24 h, whereas PRP-treated samples reached approximately 60% of the repaired area. These data were supported by collagen and elastin expression levels. In in vitro wound healing assays, lyophilized HA/PRP products exhibited a superior effect compared to PRP alone at 3 months, but no significant improvement was found after 6 months. Prolonged storage needs very low temperatures to preserve PRP features (−20°C). In conclusion, we propose novel lyophilized HA/PRP formulations as promising products for topical and intra-dermic applications, especially for wound healing. The combination of HA as a biopolymer facilitates the slow release of growth factors contained in PRP while also allowing for a prolonged shelf life under cold-controlled conditions (4°C).